Recurrent cryptococcal meningitis at Chris Hani Baragwanath academic hospital, Soweto, South Africa - Maphanga, Dineo (My University, 2017)
Background Cryptococcal meningitis (CM) remains an ongoing and devastating disease with detrimental outcomes accounting for up to 44% of acquired immune deficiency syndrome (AIDS) related mortality. A significant portion of the cases have been attributed to recurrences, thought to be largely preventable. In the first world the recurrence rate is estimated at <5% but it is more than double that rate in developing countries. In the era of freely available antiretroviral therapy (ART) and secondary prophylaxis with fluconazole, we endeavoured to study the prevalence along with the clinical and laboratory features of patients with recurrence of CM in our setting. Objectives 1. Determine the prevalence of recurrent CM at Chris Hani Baragwanath Academic Hospital (CHBAH) for patients with the incident presentation between the years 2012-2013. 2. Determine the use of ART and fluconazole in patients with recurrent CM. The patients were divided into 4 groups reliant on whether they were on ART and fluconazole at the time of diagnosis of recurrent CM. a. Patients on ART and fluconazole. b. Patients on ART alone. c. Patients on fluconazole alone. d. Patients on no therapy. 3. Describe the clinical and laboratory features of patients with recurrent CM, as a cohort and by group. The groups were comparatively analysed. The variables studied included clinical presentation, mortality and cerebrospinal fluid (CSF) findings. Methods This was a retrospective review of adult patients presenting to Chris Hani Baragwanath Academic Hospital (CHBAH) with recurrent CM. The patients were identified using the Group for Enteric, Respiratory, and Meningeal disease Surveillance for South Africa (GERMS-SA) database. This is a nationwide network of clinical microbiology laboratories (both in the public and private sector) participating in an active laboratory-based surveillance programme for bacterial and fungal pathogens of public health importance. Specimen of patients identified to have CM are submitted to the National Institute of Communicable Diseases for confirmation and further characterisation. CHBAH is one of 25 enhanced surveillance sites where additional data including demographics, clinical findings and laboratory results were recorded. Hospital records and laboratory results were used to supplement the data. Patients with recurrent CM were identified between February 2012 and April 2014. The incident episode of CM had to have been from January 2012 to December 2013. The number of incident cases in that period was the denominator for the rate of recurrence. Results A total of 51 patients were identified from the database from an incident cohort of 658 patients with CM giving a prevalence rate for recurrent CM of 7.8%. These 51 patients had a total of 62 recurrent episodes of CM. Eight (15.7%) patients had multiple recurrences. There were 30 (58.8%) males and the median CD4 count was 85/mm3 (IQR: 3-393/mm3). The median time to recurrence was 143 days (IQR: 32-633 days). Data on the use of ART and fluconazole was available for 56 (90.3%) of recurrent episodes in 45 patients. A total of 37 (66.1%) recurrent episodes were in patients on ART and 26 (46.4%) were on fluconazole. The 56 episodes of recurrent CM were grouped as follows: 1. A total of 20 (35.7%) recurrent episodes were in patients on both ART and fluconazole. Immune reconstitution syndrome (IRIS) contributed 14 cases. 2. A total of 17 (30.4%) of recurrent episodes were in patients only on ART. 3. A total of 6 (10.7%) of the recurrent episodes were in patients on fluconazole prophylaxis only. 4. A total of 13 (23.2%) of the recurrent episodes were in patients on no therapy. The patients presented clinically with headaches (76.8%), meningism (57.1%), a Glasgow Coma Scale (GCS) <15 (30.4%) and seizures (14.3%). Twenty-seven (48.2%) cases died in hospital. Mortality was significantly higher in those with a GCS of less than 15 (82% vs. 33%, P=0.0008) and those with seizures (86% vs. 42%, P=0.0197). No statistically significant differences were noted amongst the 4 groups with respect to the clinical presentation, cerebrospinal fluid profile, the time to recurrence and mortality. Conclusion The prevalence of recurrent CM was midway between that of the developed world and a pre-ART study in Gauteng. Recurrent CM had a high mortality. The finding that one-third of patients were not on ART and that more than half were not on fluconazole at the time of diagnosis of recurrent CM, together with the high rate of multiple recurrence requires further investigation. Explicit steps need to be taken to link patients with health care facilities to ensure reliable provision of fluconazole and the initiation of ART.
A research report submitted to the University of the Witwatersrand, Johannesburg in partial fulfillment for the requirements of the degree of Master of Medicine 2017.
Keywords: Cryptococcal Meningitis